Sistem pendukung keputusan pemilihan smartphone tahun 2022 menggunakan metode simple additive weighting berbasis MATLAB - Juyus Muhammad Adinulhaq; Akhmad Fathurohman; Safuan Safuan (Universitas Muhammadiyah Semarang, 2023)
This research develops a decision support system using the Simple Additive Weighting (SAW) method based on MATLAB to choose a smartphone in 2022. Based on the specified criteria and data, the best smartphone that managed to get the highest rating is the Xiaomi Redmi Note 12 Pro. This smartphone meets the criteria for price, rating, 5G features, NFC, IR Blaster, RAM capacity, internal memory, battery, screen refresh rate, and rear main camera well. This decision support system provides effective assistance in choosing a smartphone according to user preferences and needs.